Prospective of implementing Concentrating Solar Power (CSP) in Malaysia environment - Affandi, Rosnani; Gan, Chin Kim; Ab Ghani, Mohd Ruddin (IDOSI Publications, 2014)
Recently, climate change challenge and depletion of fossil fuels has prompted many countries to take these issues seriously. Promoting the use of Renewable Energy (RE) resources has become one of the top government agendas throughout the world. In this context, energy that is sustainable, economically feasible and environmentally friendly will become the priority object for further research and development. In this respect, solar energy has been the central for RE researches for the past decades. However, in order to develop RE such as Concentrating Solar Power (CSP) in tropical environments such as Malaysia, several key factors that affect the performance of this system needs to be thoroughly investigated. In light of this, research towards the successful implementation of CSP technology in Malaysia environment should be continuously carried out. Therefore, this paper aims to investigate the feasibility of implementing solar CSP in Malaysia by evaluating the CSP technologies, Meteorological data as well as Direct Solar Irradiance (DNI).